An investigation of the chemical kinetics of biogas combustion. (15th June 2015) - Fischer, M.; Jiang, X.
Highlights: Five reaction mechanisms were used for simulating ignition delay times of biogas. Three of the models reproduce reasonably well the ignition delay times of biogas blends. The formation of NO and CO has been predicted numerically under numerous conditions. The pollutant N2 O is produced for high pressures and high CO2 content in lean mixtures. Abstract: Chemical kinetic aspects of the combustion of biogas (containing CH 4, CO 2 and possibly H 2 ) have been investigated. Five reaction mechanisms were considered and tested with respect to the ignition delay times of H2 –CO2 –O2 and CH4 –CO2 –O2 mixtures measured in shock tubes. While the GRI (Gas Research Institute) mechanism 3.0 could not reproduce the first set of measurements, it brought up the best match for the second one directly relevant to biogas. Consequently it was employed for predicting the amounts of CO and NO produced under the same conditions. It was found that for stoichiometric and lean mixtures an increase in the initial CO 2 concentration lowers the production of NO and raises that of CO at higher temperatures. For rich mixtures, the production of NO is far smaller and does not follow this simple pattern. Kinetically, the reaction H + CO 2 → OH + CO plays a greater role in the presence of CO 2 and must hence be accurately known. For some conditions, the environmentally problematic N 2 O is produced. The effects of hydrogen addition on biogas have also been predicted using GRI 3.0. The addition of 2% of H 2 always raises the concentration of produced CO when compared to the mixture without hydrogen. The formation of NO is increased for higher H 2 amounts at p  = 1 bar but decreased at p  = 10 bar. Overall, the present study supports the viability of the GRI-mechanism for the simulation of biogas combustion.